Pemahaman Mahasiswa Akuntansi Terhadap Aset, Liabilitas, Dan Ekuitas Setelah Penerapan IFRS - Sufiyati; Sofia Prima Dewi; Merry Susanti (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This study was conducted to determine whether there are differences in understanding of accounting for assets, liabilities, and equity between students from SMU majoring in IPS, SMU majoring in Science, and SMK Accounting Department. Data collection methods were conducted by distributing questionnaires to students in West Jakarta and Tangerang. The questionnaires were distributed from August 28 to October 18, 2017. Data processing methods were performed by using SPSS. The results showed that there is a difference of understanding of accounting for liabilities between students who come from SMU majoring in science with SMK Accounting Department, and SMU majoring in IPS with SMK Accounting Department but for students who come from SMU majoring in science majors and SMU majoring in IPS showed no difference. Students from majoring in IPS, SMU majoring in Science, and SMK Accounting Department showed the same understanding of accounting for assets and equity.